2017
DOI: 10.1136/ejhpharm-2016-001000
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of primary non-adherence to concomitant chronic treatment in HIV-infected patients with antiretroviral therapy

Abstract: ObjectivesTo identify the independent risk factors of primary non-adherence to chronic concomitant treatment in HIV-positive patients, and to measure primary and secondary non-adherence rates to chronic treatments, and secondary non-adherence to antiretroviral therapy and the prevalence of concomitant chronic diseases.MethodsWe conducted a retrospective study that included HIV-infected patients with antiretroviral treatmentwho attended the pharmaceutical care office between January and December 2012. The depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…Further, as the number of PLWH with polypharmacy increased due to longer survival, comorbidity and co-medication are additional resultant barriers of poor adherence. [45][46][47][48] Though antiretroviral regimen complexity and pill burden were not directly evaluated in this study, we observed lower overall combined adherence when compared to adherence evaluated as medication dose, schedule, and instruction adherence separately. This finding suggested poorer antiretroviral adherence in PLWH, and supports previous reports that estimating adherence based on medication dose alone may overestimate the true adherence level.…”
Section: Discussionmentioning
confidence: 66%
“…Further, as the number of PLWH with polypharmacy increased due to longer survival, comorbidity and co-medication are additional resultant barriers of poor adherence. [45][46][47][48] Though antiretroviral regimen complexity and pill burden were not directly evaluated in this study, we observed lower overall combined adherence when compared to adherence evaluated as medication dose, schedule, and instruction adherence separately. This finding suggested poorer antiretroviral adherence in PLWH, and supports previous reports that estimating adherence based on medication dose alone may overestimate the true adherence level.…”
Section: Discussionmentioning
confidence: 66%
“…This suggests prioritization of drug intake by patients based on their beliefs and perceptions about drugs 34 . The results of the Borrego et al 35 study showed that adherence problems begin at the time of prescription, because one third of patients will not even collect the prescribed medication.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of comorbidities on polypharmacy adherence lies mainly in the number, type, and severity of comorbidities (Krentz and Gill, 2016;Borrego et al, 2018;Manzano-García et al, 2018;Gimeno-Gracia and Sanchez-Rubio-Ferrandez, 2020). Most studies showed that comorbidities could lead to a decrease in adherence to one or more medications, especially for patients with psychiatric disorders (Walkup et al, 2008;Kumar and Encinosa, 2009).…”
Section: Condition-related Factorsmentioning
confidence: 99%